Health risk assessment of fluoride in water distribution network of Mashhad, Iran. Issue 4 (19th May 2019) - Ghaderpoori, Mansour; Paydar, Maryam; Zarei, Ahmad; Alidadi, Hossein; Najafpoor, Ali Asghar; Gohary, Abdol Hamid; Shams, Mahmoud
ABSTRACT: High and low levels of fluoride in drinking waters have been considered as a major public health issue in recent years. This cross-sectional study was conducted over five consecutive years (from 2012 to 2016) in the water distribution network of Mashhad city, Iran with the objectives of determining levels of fluoride and to perform health risk assessment among residents in the study area. Water samples were taken from 30 stations and were analyzed using UV-visible spectrophotometer. The mean annual concentrations of fluoride in all stations during five years of consecutive study were lower than the respective maximum permissible limits (1.5 mg/L) in water as regulated by the WHO. The human health risk assessment was performed by calculating the chronic daily intake and hazard quotient (HQ) of fluoride through human oral intake for adults (men and women) and children for each year during a five-year study. Health risk analysis in this study presented that the non-carcinogenic risk associated with fluoride exposure through drinking water in Mashhad was mostly acceptable because the mean HQ values of fluoride were lower than 1.